Alex Sherman: capstone - Sherman, Alex, artist (Colorado State University. Libraries, 2024)
The artist's statement: As an artist, I embrace spontaneity as a driving force in my creative process. Each piece starts from a moment of inspiration—sometimes sparked by a fleeting memory, a random conversation, or a burst of emotion—and takes on a life of its own. For instance, when I created a recent abstract painting, I let my brushstrokes flow without planning, reacting to the tension of the moment. This unfiltered approach gives my work a raw, energetic quality, as though the piece itself is alive, evolving with each brushstroke and color choice. Color plays a crucial role in this process, becoming almost a character in its own right. I often gravitate toward bold, contrasting palettes that push boundaries. For example, in a recent mixed-media piece, I combined the intensity of cobalt blue with the warmth of burnt orange, creating an electrifying sense of movement. On the other hand, in more introspective works, I'll lean toward the subtlety of pastels—soft pinks, lavenders, and muted greens—to evoke a sense of calm and serenity. Each color choice reflects a mood, a feeling, or a story that I want to communicate, engaging the viewer on a visceral level. Typography and fonts also hold a place in my work, especially in pieces that merge visual art with text. I might incorporate graffiti-style lettering or digital-inspired fonts to explore the intersection of street culture and contemporary communication. For example, in a recent collage, I used a combination of bold sans-serif fonts with fragmented hand-drawn lettering, juxtaposing structured text with chaotic, free-form imagery. This integration of fonts connects my work to the broader landscape of visual culture, allowing it to speak to a wide audience by referencing the language and symbols we interact with daily. By weaving these elements together—spontaneity, color, and typography—I create visual narratives that not only express my individual perspective but also tap into the collective consciousness. Whether I'm reflecting on the power of social media in shaping public identity or simply exploring the interplay between light and shadow, my goal is to invite viewers to connect, interpret, and engage with my art in their own unique way.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design